Thin-skinned mass-wasting responsible for widespread deformation at Arenal volcano - Ebmeier, Susanna K.; Biggs, Juliet; Muller, Cyril; Avard, Geoffroy (Frontiers in Earth Science, 2014)
The shape and stability of a volcano’s edifice depends on the relationship between eruption rate and the loss or redistribution of material due to erosion, mass-wasting or deformation. This work provides measurements of deformation and shallow mass-wasting at a stratovolcano immediately after an extended period of growth, and demonstrates that high rates of deformation can be associated with shallow edifice processes. We measure displacements and surface property changes on the upper flanks of Arenal, Costa Rica, after a ~40 year period of edifice growth. We present high-resolution satellite radar imagery of the 2011-2013 period that provides evidence of frequent rockfalls and of at least 16 slow-moving, shallow landslides (estimated to be 5-11 m thick, total volume = 2.4×107 m3 DRE). The 2012 Nicoya Earthquake (Mw 7.4) had no measurable impact on the velocities of sliding units at Arenal, but did result in an increase in the area affected by rockfall.